REFORMS AND INVESTMENTS IN THE FIELD OF MODERN ARCHITECTURE AND CONSTRUCTION OF UZBEKISTAN (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article discusses the reforms implemented in the field of construction and architecture in Uzbekistan and the role and importance of investments in these reforms.